Impact of economic freedom distance on India's inbound cross-border acquisition volume: Moderating role of economic distance - Chandrika Raghavendra; Mahesh Rampilla; Venkata Ramana Thanikella; Isha Gupta (Journal of Risk and Financial Management, 2023)
Cross-border acquisitions (CBA) are a form of foreign direct investments and have been dramatically increasing over the last three decades. India has been one of the top CBA destinations among emerging economies, making it interesting to explore the determinants. Even though the CBA research is voluminous, the role of economic freedom is understudied. In this background, by extending the knowledge of distance measures impacting cross-border acquisition (CBA) activities, we examine the impact of economic freedom distance on India's inbound CBA volume and the moderating role of economic distance. We used a sample of 979 observations by collecting the CBA data from Thomson's EIKON Mergers and Acquisitions database for our study period covering 1990 to 2020. We show that economic freedom distance negatively impacts India's inbound CBA volume. Moreover, economic distance significantly moderated their effect. These results indicate that India should strengthen its economic freedom and grow steadily to attract more CBA volume inflow. These findings have important theoretical and practical implications for multinational firms and policymakers in making emerging economies like India an attractive destination for CBA activities.
Keywords: 650; India; cross-border acquisitions; economic distance; economic freedom